The Omnibus Method: Challenges in the Legislative Process - Anggraeni, Ricca (Fakultas Hukum Universitas Lampung, 2024)
The Omnibus Law in the Job Creation Law marks the beginning of the use of the omnibus method in Indonesia’s legislative process, aimed at reducing the country’s excessive regulatory framework. The law was reviewed by the Constitutional Court, which declared it conditionally unconstitutional, requiring amendments within two years. Failure to comply would result in the law becoming permanently unconstitutional, with repealed provisions reinstated. In response, Undang-Undang Pembentukan Peraturan Perundang-undangan was amended to include the omnibus method in legislative formulation. As a result, other laws, such as the Health Act and the Financial Sector Development and Strengthening Act, have also adopted this approach. However, a key challenge is the need for laws created through the omnibus method to be revised using the Omnibus re-method, highlighting the difficulties in applying the omnibus method in response to evolving legal and societal needs.